(untitled) (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: To evaluate the shear bond strength of three different resin cements: self-etching (P), etch-and-rinse (R) and self-adhesive (U), to enamel and dentin using two types of restorative materials. Methods: One hundred twenty bovine incisors had the buccal surface ground to obtain a flat and smooth surface of approximately 25 mm2. Half of the specimens had the enamel exposed (E), and the other half had the dentin exposed (D). An ad-hesive tape with a 3 mm-diameter orifice delimited the bonding area. Sixty 3 x 3 mm lithium disilicate glass-ceramic cylinders (C) and 60 indirect composite resin cylinders (R) were cemented to enamel or dentin using three types of resin cements, resulting in 12 experimental groups represented by symbols allusive to treatment protocols: PEC; PER; PDC; PDR; REC; RER; RDC; RDR; UEC; UER; UDC; and UDR. Shear bond strength test was performed with a crosshead speed of 0.5 mm/min. The data were subjected to ANOVA and Tukey’s test with a significance level of 5%. Results (MPa ± DP): the highest mean value obtained, REC group (17.46 ± 3.29), differed significantly from others, except for the PEC group (14.60 ± 5.88). Among the groups with lower mean values, there was a predominance of those where the indirect resin was used regardless the substrate and type of resin cement, and the UDR group (1.03 ± 1.03) was statistically different from the others. Conclusion: In this study, all three experimental variables tested influenced the shear bond strength of tooth-cement-restoration interfaces.